REVIEW OF DIFFERENCES OF POPULATION DATA WHICH ARE REQUIREMENTS FOR PASSPORT APPLICATION AND DEVELOPMENT OF ONLINE PASSPORT REGISTRATION (APAPO) APPLICATIONS AS A SOLUTION TO THE CLASS II IMMIGRATION OFFICE OF TPI TAREMPA - Renra Hata Galih; Abdi Adirahim Hafidz (Polteknik Imigrasi, 2020)
The difference in population data that is a requirement in the application for a Travel Document of the Republic of Indonesia (Passport) is one of the problems that often occurs in the immigration service process at the TPI Tarempa Class II Immigration Office. waters. As one of the immigration technical service units for the community in the Anambas Islands Regency, it is a separate obligation for the Class II TPI Tarempa Immigration Office to be present to provide a solution to this problem. Furthermore, to analyze the problem the author will use the service standards in Law Number 23 of 2006 concerning Population Administration and Regulation of the Minister of Law and Human Rights Number 8 of 2014 concerning Ordinary Passports and Travel Letters Like Passports and Regulation of the Director General of Immigration Number: IMI-UM.01.01 -4166 About the Implementation of Online Passport Registration throughout Indonesia to determine the right solution to this problem. The results of this study are the Online Passport Registration Application (APAPO) can be the right solution by adding certain features for population data checks.